Problematika Guru Al-Quran Hadis dalam Menggunakan Media Pembelajaran Berbasis Digital di MTsN 3 Padang Lawas - Pasaribu, Zakiyah Khairani; Pulungan, Juli Julaiha; Sapri (Ikatan Da'i Indonesia, 2024)
The purpose of this study is to find out the skills/abilities and obstacles of Al-Quran Hadith teachers in using digital-based learning media and to describe the efforts of Al-Quran Hadith teachers in overcoming obstacles in the use of digital-based learning media This study uses a qualitative method with a descriptive approach. Data were collected through observations, interviews, and documentation studies. Data analysis includes data reduction, data presentation, and conclusion drawn, which is carried out gradually during the study. The validity of the data is checked by credibility tests through increased diligence in data collection, triangulation, case analysis of findings, and objectivity. The results of the study show that the skills of Al-Quran Hadith teachers at MTsN 3 Padang Lawas in using digital learning media are not optimal. Difficulties in technology and limited equipment hinder learning. The difference in the number of teachers and equipment, as well as the inability of some teachers, especially the older ones, are inhibiting factors. Of the five teachers, only three are able to use digital media, while the other two rely on non-digital media. The main obstacle is the lack of knowledge and skills in technology and time management. Efforts to overcome obstacles include self-study, IT training, increasing motivation, and time management.